Towards a Zero-Emissions Port Stay; Challenges, Opportunities, and Insights from the Industry - Zis, Thalis (My University, 2023)
This paper is concerned with the prospects of a potential zero emissions port stay for international ships calling at different ports. We focus primarily on shorepower provision and examine other technological solutions that can be useful in reducing the environmental footprint of port stays. We review academic literature on the subject, where it is evident that the interest on such technological solutions is on the rise. Three key stakeholders are identified in the attempt to reduce emissions from ships at ports. These groups are the port operators, the shipping companies, and the technology or solution providers that reduce emissions. To understand their challenges, their differences, as well as potential synergies, we launched a survey that targeted their views and experiences with the use of emissions abatement technologies. It is evident from the survey that the environmental aspects of port stays are seeing an increasing attention, but the main challenges are still not addressed by the existing solution space. The main challenges and barriers to the further development of shorepower solutions for international shipping are presented, and key differences across different sectors are briefly discussed. In the current uncertain environment with extreme increases in fuel and electricity prices, it is not easy to consider low-carbon solutions in the shipping sector. However, the increased pressure for environmental action, and the potential use of Market-Based Measures (MBMs) can help the transition by acting as an equalizer for the associated economics of energy provision at the port.